2016
DOI: 10.1108/ijis-07-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of innovation capability in supply chain: an exploratory study

Abstract: Purpose The purpose of this paper is to explore the development of innovation capability construct measures in the context of supply chain and to objectively identify the key dimensions for stimulating focal firms’ innovativeness. Design/methodology/approach The scale items for this research were obtained from extant literature. The data were collected from homogenous sample of 117 Ghanaian middle level managers (respondents). Exploratory factor analysis was used to identify the main dimensions of innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
3
16
0
1
Order By: Relevance
“…It seems to be concluded that most of the KPI variables are correlated to each other. This confirms that factor analysis can be used with this data (Iddris, 2016;Vanichbuncha, 2010). The KPIs are analyzed to classify KPI groups.…”
Section: Results Of Exploration Factor Analysis For Sustainable Port supporting
confidence: 77%
“…It seems to be concluded that most of the KPI variables are correlated to each other. This confirms that factor analysis can be used with this data (Iddris, 2016;Vanichbuncha, 2010). The KPIs are analyzed to classify KPI groups.…”
Section: Results Of Exploration Factor Analysis For Sustainable Port supporting
confidence: 77%
“…From the normality test that has been done, the following results are obtained: There is an influence of innovation capability on supply chain integration From the data analysis that has been done with the SEM method, the results show that there is a significant influence between innovation capability and supply chain integration. These results support the research conducted by Iddris (2014), Ferrer (2011), Ayoub (2017, Desbarats (1999), Iddris (2016), Khalfan (2006), Liao (2018), Lii (2016), Dinwoodie (2014 ) and Yunus (2018) who also stated that innovation capability can influence supply chain integration.…”
Section: Analysis and Discussionsupporting
confidence: 88%
“…Some literature states that by having an innovation capability, the company will be able to improve supply chain management, especially in supply chain integration. The relationship between innovation and supply chain integration is supported by several literatures namely Iddris (2014), Ferrer (2011), Ayoub (2017, Desbarats (1999), Iddris (2016), Khalfan (2006), Liao (2018), Lii ( 2016), Dinwoodie (2014) and Yunus (2018) which states that the ability of innovation is able to increase supply chain integration, both directly and together with other variables. Therefore this study proposes the following hypothesis: H1: Innovation capability has a significant effect on supply chain integration.…”
Section: Innovation Capability and Supply Chain Integrationmentioning
confidence: 82%
“…SCI has also been defined as "a change (incremental or radical) within the supply chain (SC) network, SC technology, or SC processes (or combination of those) that can take place in a company function, within a company, in an industry or in a SC in order to enhance new value creation for the stakeholder" (Arlbjorn et al, 2011, p. 8). Therefore, SCI implies the exchange of skills, expertise, and resources among key SC members since a firm might not possess all the resources and capabilities needed for innovation processes (Iddris, 2016). Consequently, trust, information-sharing and learning are essential factors for enabling fruitful SCI (Ojha et al, 2016).…”
Section: Supply Chain Innovation (Sci)mentioning
confidence: 99%